Clinicopathological findings of pediatric NTRK fusion mesenchymal tumors - Jeongwan Kang; Jin Woo Park; Jae-Kyung Won; Jeong Mo Bae; Jaemoon Koh; Jeemin Yim; Hongseok Yun; Seung-Ki Kim; Jung Yoon Choi; Hyoung Jin Kang; Woo Sun Kim; Joo Heon Shin; et al. (Diagnostic Pathology, 2020)
Abstract Background While ETV6- NTRK3 fusion is common in infantile fibrosarcoma, NTRK1/3 fusion in pediatric tumors is scarce and, consequently, not well known. Herein, we evaluated for the presence of NTRK1/3 fusion in pediatric mesenchymal tumors, clinicopathologically and immunophenotypically. Methods We reviewed nine NTRK fusion-positive pediatric sarcomas confirmed by fluorescence in situ hybridization and/or next-generation sequencing from Seoul National University Hospital between 2002 and 2020. Results One case of TPR-NTRK1 fusion-positive intracranial, extra-axial, high-grade undifferentiated sarcoma (12-year-old boy), one case of LMNA-NTRK1 fusion-positive low-grade infantile fibrosarcoma of the forehead (3-year-old boy), one case of ETV6-NTRK3 fusion-positive inflammatory myofibroblastic tumor (IMT) (3-months-old girl), and six cases of ETV6-NTRK3 fusion-positive infantile fibrosarcoma (median age: 2.6 months, range: 1.6–5.6 months, M: F = 5:1) were reviewed. The Trk immunopositivity patterns were distinct, depending on what fusion genes were present. We observed nuclear positivity in TPR-NTRK1 fusion-positive sarcoma, nuclear membrane positivity in LMNA-NTRK1 fusion-positive sarcoma, and both cytoplasmic and nuclear positivity in ETV6-NTRK3 fusion-positive IMT and infantile fibrosarcomas. Also, the TPR-NTRK1 fusion-positive sarcoma showed robust positivity for CD34/nestin, and also showed high mitotic rate. The LMNA-NTRK1 fusion-positive sarcoma revealed CD34/S100 protein/nestin/CD10 coexpression, and a low mitotic rate. The IMT with ETV6-NTRK3 fusion expressed SMA. Six infantile fibrosarcomas with ETV6-NTRK3 fusion showed variable coexpression of nestin (6/6)/CD10 (4/5)/ S100 protein (3/6). Conclusions All cases of NTRK1 and NTRK3 fusion-positive pediatric tumors robustly expressed the Trk protein. A Trk immunopositive pattern and CD34/S100/nestin/CD10/SMA immunohistochemical expression may suggest the presence of NTRK fusion partner genes. LMNA-NTRK1 fusion sarcoma might be a low-grade subtype of infantile fibrosarcoma. Interestingly, more than half of the infantile fibrosarcoma cases were positive for S100 protein and CD10. The follow-up period of TPR-NTRK1 and LMNA-NTRK1 fusion-positive tumors are not enough to predict prognosis. However, ETV6-NTRK3 fusion-positive infantile fibrosarcomas showed an excellent prognosis with no evidence of disease for an average of 11.7 years, after gross total resection of the tumor.